Catatonia — evolution of views and current understanding (literature review) - V. V. Dunaevsky; A. V. Kuznetsov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The literature review describes history of views on catatonia from Kahlbaum to present time. Descripted as a discrete disease by Karl Kahlbaum, since Kraepelin’s and Bleuler’s works catatonia was associated with schizophrenia for many years. At the present time catatonia is classified as a nonspecific syndrome, which can be observed in many mental diseases. Despite of common view on catatonia as a rare disease, a lot of studies show that this state is very frequent. Catatonia remains an underdiagnosed syndrome. Prompt recognition of catatonia is important since this state is life-threatening and catatonic patients need correct treatment. This article describes some diagnostic scales, used to recognize catatonia in psychiatric patients.